What goes around, comes around: job referrals through relation between social ties and organizational citizenship behavior - White, Sean R (2012)
What types of citizenship behavior and ties are associated with teammates’ disposition to refer someone to a professional project? Assuming that referral hiring is a strategy to overcome information assymetries in the selection process and that referals are made according to the assessment of a professional’s demonstrated contributions to team performance, I study both network configurations in teams and evaluations of Organizational Citizenship Behavior (OCB) to identify which are associated with colleagues’ disposition to provide these professional with a job referral. Ties are evaluated in terms of Contact Frequency and Perceived Closeness, while OCB is studied using Williams & Anderson’s (1991) factors, where OCB is presented in terms of being in-role (IRB) and extra-role, where extra-role is subdivided in behavior directed to the individual (OCBI) and behavior directed toward the group (OCBO). I study the associations between OCB and tie characteristics. I also introduce the concept of Tie Salience, which is a measure of the intensity of the tie relative to the other ties present in the group in which the dyad is embedded, finding that salience plays an importante role in building a tie within a team. I test the model through Structural Equations estimated on data obtained through a survey and find a system that regulates building personal relationships with group interests. I also find significant effects of Extra-Role behavior on Perceived Closeness.